ANALISIS PENGARUH HARGA, PELAYANAN, DAN PERSEPSI REPUTASI TERHADAP LOYALITAS MENGGUNAKAN JASA OJEK ONLINE (Survei pada Pelanggan Go-Jek Kota Solo) - Nusantara, Reva Anggun; Alwi Suddin, Sumaryanto & (Universitas Slamet Riyadi, 2018)
This study aims to analyze the significance of the influence of price, service, and reputation perception variables on the loyalty of Go-Jek customers in Solo city and analyze dominant influencing variables. Types of survey research, types of qualitative and quantitative data. Data sources are primary data and secondary data. The population of all Go-Jek customers in Solo is the February 2018 period whose numbers are unknown. Sample of 100 respondents with purposive sampling technique. The collection technique uses observation, questionnaire and literature study. Data analysis techniques: multiple linear regression analysis, t test, F test, and determination coefficient (RÂ²). The results of the validity and reliability test showed that all statements regarding price, service, perception of reputation, and customer loyalty were declared valid because of the p-value < 0.05, and reliable because Conbach's Alpha > 0.60. The results of the classical assumption test show that all variables have escaped from multicollinearity, heteroscedasticity, autocorrelation and normal distribution. Price regression analysis (X1) has a dominant influence on customer loyalty Go-Jek. Price variable (X1), service (X2) and reputation perception (X3) significantly influence the loyalty of Go-Jek customers in Solo City.Keywords: price, service, perception of reputation, customer loyalty